The tooth book - LeSieg, Theo 1904-; Mathieu, Joe 1949-.; Seuss Dr. (New York Random House, 2000)
Rhyming text and illustrations briefly point out what animals have teeth, their uses, and how to care for them.
On board pages.
Keywords: Teeth -- Fiction; Stories in rhyme